Silicon deficiency and the adaptation of tropical rice ecotypes - Winslow, M.D.; Okada, Kensuke; Correa Victoria, Fernando J. (Springer, 1997)
Although silicon (Si) is found at much higher concentrations in healthy rice crops than N, P or K, it has received far less study, particularly for upland rice. There are few reports on the existence, causes, and effects of varying Si supplies in different environments. Chemical analyses of soil, water and plant tissue samples from experiments grown on a typical weathered, acidic upland soil in Colombia found concentrations of Si which were 80-90% lower than those in a typical lowland environment. These results corroborate published findings from West Africa and Hawaii, and lend support to a conclusion that acid-soil upland rice environments in the tropics tend to be deficient in Si, increasing disease damage, among other effects. Critical values for diagnosis of Si deficiency in soils, water and rice husk tissue are suggested. These are reasonably consistent with, but extend the application of previously published values derived from lowland rice studies to upland environments, and use simpler sampling and analysis methods. A strong correlation was found (r = -0.91) between high husk Si concentration and low husk discoloration disease damage, among diverse rice genotypes grown in the uplands. These genotypic differences were mainly explained by their ecotypic affinities: those belonging to the tropical japonica ecotype exhibited 93% higher husk Si concentrations than indica ecotypes (ecotypic means of 23 vs. 12 mg kg-1 ). This is consistent with a hypothesis that the tropical japonicas may have adapted to Si deficiency in their native upland environment by evolving mechanisms to attain relatively higher tissue Si concentrations than indicas, which are believed to have evolved in the lowlands, where the Si supply is generally ample. Increased understanding of Si-mediated disease resistance in different rice environments and ecotypes could help breeders combine the high yield potential of indica types with the more durable disease resistance of the japonicas, and could contribute to the development of integrated disease management strategies.